Brunon of Querfurt, missionary to non-Slavic peoples - Tyszkiewicz, Jan (Balcanica Posnaniensia. Acta et studia, 2009)
The author's aim is to reconstruct the chronology of Bruno of Querfurt's missionary expeditions and to assess their religious and political significance. Particular attention is paid to his travels to the Kingdom of Hungary, Poland, Kievan Rus' and the nomadic Pechenegs, as well as to the role of his contacts with rulers – King Stephen I, Bolesław Chrobry and Vladimir the Great. The analysis is based on narrative sources, especially Bruno's own writings, as well as hagiographic and chronicle texts written in Hungary, Poland and Rus. The author applied source criticism, comparing different writing traditions and pointing out the difficulties associated with unclear chronology and the bias of the accounts. The main findings include confirmation of Bruno's three visits to Poland (1005–1006, 1007, 1008–1009), correction of the dates of his mission in Hungary, and proof that the expedition to the Pechenegs began from Polish territory, not Hungary. The author emphasises that Bruno's activities were strictly missionary in nature and did not serve political purposes, although they were sometimes linked to the international context. The conclusions point to Bruno's importance as a witness and participant in the Christianisation of the European borderlands, whose literary legacy and missionary activities document the religious and cultural changes of the era.